Fireproof composite low-voltage cable and preparation method thereof

By using modified flame retardants and fillers in composite cables, a dense protective layer and carbon layer is formed, which solves the problem of bacterial growth, mold and mice eating in harsh environments of the cable, and improves the flame retardancy. Antibacterial and waterproof properties extend the service life of the cable.

CN119181538AActive Publication Date: 2024-12-24QIYUAN ELECTRIC CO LTD

Patent Information

Application Number
CN202411297129.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-24
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

Existing composite cables are prone to breed bacteria and mold in harsh environments, resulting in a decrease in mechanical properties. The flame retardant performance of polyurethane materials is poor and is easily chewed by mice and insects, resulting in a decrease in the protective performance of the outer sheath and cannot meet the strict requirements. Demanding usage requirements.

Method used

Modified flame retardant and modified filler are used to improve flame retardant performance through sodium sulfonate, phosphoramide structure and cinnamide structure, and nano calcium carbonate, sorbate and isocyanate groups to improve antibacterial and waterproof properties to form a dense The protective layer and carbon layer prevent combustion and microbial erosion.

Benefits of technology

It significantly improves the flame retardancy, antibacteriality and waterproofness of the cable, enhances the mechanical properties of the outer sheath, prevents mice from eating, and extends the service life of the cable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119181538A_ABST
    Figure CN119181538A_ABST
Patent Text Reader

Abstract

The invention relates to a fireproof composite low-voltage cable, and relates to the technical field of composite cable preparation, and the fireproof composite low-voltage cable comprises a cable A, a signal line B, a belting layer C and an outer sheath D; the outer sheath D is made of a polyurethane cable material; and the polyurethane cable material comprises the following raw materials in parts by weight: 45-55 parts of thermoplastic polyurethane, 10-15 parts of an ethylene-vinyl acetate copolymer, 15-25 parts of a modified flame retardant, 3-5 parts of an antioxidant, 2-4 parts of a lubricant, 1-3 parts of a light stabilizer and 10-12 parts of a modified filler. Molecules of the modified flame retardant comprise a sodium sulfonate group, a phosphamide structure and a cinnamamide structure, so that the flame retardance and the rat-proof property of the cable are improved. Molecules of the modified filler comprise nano calcium carbonate, sorbate groups, fluorine-containing alkane long chains and the like, so that the mechanical property, antibacterial property and waterproofness of the cable are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of composite cable preparation, and in particular, relates to a fireproof composite low-voltage cable and a preparation method thereof. Background Art

[0002] With the rapid development of data communication and information technology, people have higher and higher requirements on the performance of cables. Cables that integrate signal lines and power lines are widely used. They can not only transmit current but also transmit optical signals and other signals. For this kind of composite cable, it is necessary not only to effectively shield the power transmitted by the power line and the signal transmitted by the signal line, but also to shield the external interference signal during the signal transmission through the line, and also to avoid the signal in the line from interfering with the external environment. In the composite cable, the outer periphery of the current-carrying conductor in the power line is usually coated with an insulating layer, and the outer periphery of the signal line is coated with a shielding layer, a heat insulation layer, etc. The outer sheath is located at the outermost layer of the composite cable. The protective effect of the cable outer sheath coated on the outer periphery of the signal line and the power line is extremely important for maintaining the performance of the composite cable.

[0003] Thermoplastic polyurethane materials are widely used in cable sheath materials because of their excellent wear resistance, oil resistance, low-temperature flexibility and elasticity. However, when used in harsh environments such as water bubbles, river banks, and docks, cable sheath materials are prone to breed bacteria and mold under hot and humid conditions, resulting in a sharp decline in mechanical properties. If cracks appear in the cable sheath, bacteria and mold will further enter the sheath and destroy the structure, thereby reducing the safety of the cable and shortening the service life of the cable. In addition, the flame retardant properties of polyurethane materials are not good. The outer sheath material of the cable made of polyurethane material is located in the outermost layer, which is easily eaten by rats, insects and ants, resulting in a decrease in the protective performance of the outer sheath. Therefore, it is urgent to develop a suitable modification method to improve the antibacterial, waterproof, flame retardant, and rodent-proof properties of thermoplastic polyurethane sheath materials in order to obtain composite cables with excellent comprehensive performance to meet the increasingly stringent use requirements. Summary of the invention

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] A fireproof composite low-voltage cable, comprising a cable, a signal line, a tape layer and an outer sheath; a plurality of the cable lines and a plurality of the signal lines are evenly placed in the tape layer, the tape layer is coated on the outer periphery of the cable line and the signal line, and the outer sheath is coated on the outer periphery of the tape layer;

[0006] The innermost layer of the cable is a copper conductor, and the outer periphery of the copper conductor is covered with an insulating layer; the insulating layer is made of cross-linked polyethylene material;

[0007] The innermost layer of the signal line is an optical fiber core bundle, and the outer periphery of the optical fiber core bundle is covered with a shielding layer, a heat insulation layer, and an optical cable sheath tube in sequence; the shielding layer is made of an electric shielding wire and a magnetic shielding wire woven into a mesh structure, the electric shielding wire is a copper wire, and the magnetic shielding wire is an iron wire; the heat insulation layer is made of silicone rubber, and the optical cable sheath tube is a nylon loose tube;

[0008] The tape layer is obtained by wrapping with a polyester tape;

[0009] The outer sheath is made of polyurethane cable material, which includes the following raw materials in parts by weight: 45-55 parts of thermoplastic polyurethane, 10-15 parts of ethylene-vinyl acetate copolymer, 15-25 parts of modified flame retardant, 3-5 parts of antioxidant, 2-4 parts of lubricant, 1-3 parts of light stabilizer and 10-12 parts of modified filler; the antioxidant is a mixture of antioxidant 1010 and antioxidant 618 in a mass ratio of 3:1, the lubricant is polyethylene wax, and the light stabilizer is 2,2'-hydroxy-4-methoxybenzophenone;

[0010] The preparation of the fireproof composite low-voltage cable comprises the following steps:

[0011] Step S1: extruding a cross-linked polyethylene material around the outer periphery of a copper conductor to form an insulating layer to obtain a cable;

[0012] Step S2: copper wires and iron wires are braided into a mesh structure and then coated on the outer periphery of the optical fiber core bundle to form a shielding layer; silicone rubber is then extruded on the outer periphery of the shielding layer to form a heat insulation layer; and nylon loose tube is then coated on the outer periphery of the heat insulation layer to form an optical cable sheath tube to obtain a signal line;

[0013] Step S3: adding ethylene-vinyl acetate copolymer, modified flame retardant, antioxidant, lubricant, light stabilizer and modified filler to a high-speed mixer, stirring at a speed of 250-300 r / min and a temperature of 80-90° C. for 10-20 min to obtain a mixture, transferring the mixture to an internal mixer, adding thermoplastic polyurethane and internal mixing for 8-10 min to obtain a polyurethane cable material;

[0014] Step S4: evenly place a number of cables and a number of signal lines, wrap the outer circumference of the cables and the signal lines with polyester tape to form a tape layer; then extrude the polyurethane cable material on the outer circumference of the tape layer to form an outer sheath, and obtain a fireproof composite low-voltage cable.

[0015] The modified flame retardant is prepared by the following steps:

[0016] Step a1: In a nitrogen atmosphere, sodium benzaldehyde-2-sulfonate and acetic anhydride are added to a reaction bottle, refluxed and stirred, and the temperature is raised to 150-170° C., and potassium carbonate is added, and the reaction is stirred under reflux at a constant temperature for 24-26 hours, and the alkenyl carboxylic acid is extracted, rotary evaporated, and dried to obtain the alkenyl carboxylic acid; the alkenyl carboxylic acid is added to DMF, and dithionyl chloride is added under stirring, and the reaction is stirred under reflux at 50° C. for 4-5 hours to obtain the acyl chloride product;

[0017] Further, the dosage ratio of benzaldehyde-2-sulfonate sodium, acetic anhydride, and potassium carbonate is 0.1 mol: 0.05-0.07 mol: 0.005-0.008 mol; the dosage ratio of alkenyl carboxylic acid, DMF, and dichlorothionyl is 0.1 mol: 65-75 mL: 0.12-0.15 mol;

[0018] During the reaction of step a1, the aldehyde group of sodium benzaldehyde-2-sulfonate reacts with acetic anhydride to generate an alkenyl carboxylic acid containing a sodium sulfonate group; the carboxyl group of the alkenyl carboxylic acid reacts with thionyl chloride to generate an acyl chloride product;

[0019] Step a2: Add N-aminoethylpiperazine, potassium carbonate and dimethyl sulfoxide into a flask to obtain a mixed solution 1, then add the acyl chloride product into dimethyl sulfoxide to obtain a mixed solution 2, slowly dropwise add the mixed solution 2 into the mixed solution 1 in an ice-water bath at 0°C, after the dropwise addition is completed, heat to 40°C, stir and react at a constant temperature for 8-10 hours, and distill under reduced pressure to obtain an amide product;

[0020] Further, the dosage ratio of N-aminoethylpiperazine, potassium carbonate, and dimethyl sulfoxide is 0.1 mol: 0.002-0.004 mol: 25-35 mL; the dosage ratio of the acyl chloride product and dimethyl sulfoxide is 0.1 mol: 75-85 mL; the dosage ratio of the mixed solution 1 and the mixed solution 2 is 30-40 mL: 80-90 mL;

[0021] During the reaction of step a2, the acyl chloride product reacts with the primary amino group of N-aminoethylpiperazine to generate an amide product;

[0022] Step a3: Add phenylphosphoryl dichloride to toluene, then add the amide product, stir at 0-5°C for 2h, then heat to 40-50°C, reflux and react at constant temperature for 1h, filter, extract and dry to obtain a modified flame retardant;

[0023] Further, the usage ratio of phenylphosphoryl dichloride, toluene, and amide product is 0.1 mol: 260-270 mL: 0.2 mol;

[0024] During the reaction of step a3, phenylphosphoryl dichloride reacts with the secondary amino group of the amide product to generate a modified flame retardant containing phosphoramide.

[0025] The modified filler is prepared by the following steps:

[0026] Step b1: adding nano calcium carbonate to ethanol, ultrasonically dispersing for 30 minutes, obtaining solution 1 and adding it to a three-necked flask, then adding linoleic acid to the ethanol, stirring at 50-60° C. for 35-45 minutes, obtaining solution 2 and adding it to the three-necked flask, turning on reflux stirring and reacting at 70-80° C. for 1-1.5 hours, and then filtering, drying and grinding to obtain modified calcium carbonate;

[0027] Further, the dosage ratio of nano calcium carbonate to ethanol is 10 g: 30-40 mL, the dosage ratio of linoleic acid to ethanol is 0.1 mol: 60-70 mL, the dosage ratio of solution 1 to solution 2 is 35-45 mL: 65-75 mL, and the volume fraction of ethanol is 95%;

[0028] During the reaction of step b1, linoleic acid wet-modifies nano-calcium carbonate to obtain modified calcium carbonate having long alkane chains with unsaturated double bonds on the surface;

[0029] Step b2: Add modified calcium carbonate to dichloromethane, start stirring, then add 3-chloroperoxybenzoic acid, stir and react at room temperature for 4-5 hours to obtain the epoxy product; in a nitrogen atmosphere, add sorbic acid and ethanol to a flask, heat to 45°C, add pyridine, start stirring, add the epoxy product to the flask, stir and react for 8-10 hours, then heat to 105-115°C, stir for 1-2 hours to obtain the esterification product;

[0030] Further, the dosage ratio of modified calcium carbonate, dichloromethane and 3-chloroperoxybenzoic acid is 12-14 g: 50-60 mL: 0.1 mol; the dosage ratio of sorbic acid, ethanol, pyridine and epoxidation product is 0.2 mol: 80-90 mL: 0.020-0.025 mol: 25-27 g, and the volume fraction of ethanol is 95%;

[0031] During the reaction of step b2, the unsaturated carbon-carbon double bonds in the modified calcium carbonate are oxidized into epoxy groups to obtain epoxy products; the carboxyl groups of sorbic acid react with the epoxy groups of the epoxy products to form an esterification product containing alcoholic hydroxyl groups;

[0032] Step b3: After mixing the esterification product and isocyanate, add 20% by mass of dilute sulfuric acid solution and methanol, and react at 50° C. for 4 hours to obtain a modified filler;

[0033] Further, the amount ratio of the esterification product, the isocyanate, the dilute sulfuric acid solution with a mass fraction of 20% and the methanol is 30-32 g: 0.2 mol: 100 mL: 300-320 mL, and the isocyanate is 3,3,4,4,5,5,6,6,7,7,8,8,9,9,10,10,10-heptadecafluorodecyl isocyanate;

[0034] During the reaction process of step b3, the alcohol hydroxyl group of the esterification product reacts with isocyanate to obtain a modified filler.

[0035] Beneficial effects of the invention: The invention discloses a fireproof composite low-voltage cable, comprising a cable line, a signal line, a tape layer and an outer sheath; the outer sheath is made of a polyurethane cable material, and the polyurethane cable material comprises the following raw materials: thermoplastic polyurethane, ethylene-vinyl acetate copolymer, modified flame retardant, antioxidant, lubricant, light stabilizer and modified filler.

[0036] The modified flame retardant molecule contains sodium sulfonate group, phosphoramide structure, and cinnamamide structure; the sulfur element in the sodium sulfonate group generates non-combustible gases such as sulfur dioxide when burning, dilutes the concentration of combustible gas, and solidifies in the carbon layer in the form of sodium sulfate and sodium sulfite compounds, forming a dense and thick protective carbon layer, reducing the heat transfer of the burning part, and effectively preventing the further combustion of the matrix in the gas phase and solid phase, while inhibiting the release of smoke; the phosphoramide structure generates phosphorus-containing compounds when burning, promotes the formation of a carbon layer, and is coated on the surface of the polymer. The carbon layer is non-combustible, oxygen-insulated, and has poor thermal conductivity, which prevents continued combustion. At the same time, non-combustible gas is generated to dilute the combustible gas, which has a coordinated effect of phosphorus-nitrogen flame retardancy, and cooperates with the sodium sulfonate group in the same molecule to quickly prevent the combustion from continuing, and has excellent flame retardant performance; the cinnamamide structure not only does not produce toxic substances and odors that are harmful to the human body and pollute the environment, but also can long-term avoid mice, preventing mice from gnawing on the outer sheath material so that the outer sheath loses its protective effect. Therefore, the modified flame retardant makes the cable have excellent flame retardancy and rodent resistance.

[0037] The modified filler molecules contain nano-calcium carbonate, sorbate groups, fluorinated alkane long chains and isocyanate groups. The hydrophilic and oleophobic properties of the surface of nano-calcium carbonate in the modified filler are improved, it is not easy to agglomerate, the dispersion compatibility in the matrix is ​​enhanced, and the mechanical properties of the outer sheath are improved; compared with sorbic acid, which is difficult to enter microbial cells because it is easy to form ions under neutral and alkaline conditions, sorbate is less affected by acidity and alkalinity and has a stronger affinity with microbial membranes, and is easier to penetrate into microbial cells, so it has stronger antibacterial properties; the fluorinated alkane long chain has strong hydrophobicity, which can prevent water from penetrating into the outer sheath, causing the insulation and other properties of the cable to be adversely affected; the isocyanate group is similar to the structure of thermoplastic polyurethane, which helps to disperse the modified filler in the matrix. Therefore, the modified flame retardant enhances the mechanical properties, antibacterial properties and waterproof properties of the cable. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0039] Figure 1 This is a structural schematic diagram of a fireproof composite low-voltage cable of the present invention.

[0040] In the accompanying drawings, the components represented by the reference numerals are listed as follows:

[0041] A, cable, AⅠ, copper conductor, AⅡ, copper conductor;

[0042] B, signal line, BⅠ, optical fiber core bundle, BⅡ, shielding layer, BⅢ, thermal insulation layer, BⅣ, optical cable sheath;

[0043] C, tape layer; D, outer sheath; DETAILED DESCRIPTION

[0044] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] Example 1: A modified flame retardant, the preparation of which comprises the following steps:

[0046] Step a1: In a nitrogen atmosphere, sodium benzaldehyde-2-sulfonate and acetic anhydride are added to a reaction bottle, reflux and stir, heat to 150°C, and then potassium carbonate is added. The reaction is stirred at constant temperature for 24 hours, and the alkenyl carboxylic acid is obtained by extraction, rotary evaporation, and drying. The alkenyl carboxylic acid is added to DMF, and dithionyl chloride is added under stirring. The reaction is refluxed and stirred at 50°C for 4 hours to obtain an acyl chloride product. The dosage ratio of sodium benzaldehyde-2-sulfonate, acetic anhydride, and potassium carbonate is 0.1 mol: 0.05 mol: 0.005 mol; the dosage ratio of alkenyl carboxylic acid, DMF, and dithionyl chloride is 0.1 mol: 65 mL: 0.12 mol.

[0047] Step a2: N-aminoethylpiperazine, potassium carbonate and dimethyl sulfoxide are added to a flask to obtain a mixed solution 1, and then the acyl chloride product is added to dimethyl sulfoxide to obtain a mixed solution 2. The mixed solution 2 is slowly added dropwise to the mixed solution 1 in an ice-water bath at 0°C. After the addition is completed, the mixture is heated to 40°C, stirred at a constant temperature for 8 hours, and distilled under reduced pressure to obtain an amide product. The amount ratio of N-aminoethylpiperazine, potassium carbonate and dimethyl sulfoxide is 0.1 mol: 0.002 mol: 25 mL; the amount ratio of the acyl chloride product and dimethyl sulfoxide is 0.1 mol: 75 mL; the amount ratio of the mixed solution 1 to the mixed solution 2 is 30 mL: 80 mL;

[0048] Step a3: Add phenylphosphoryl dichloride to toluene, then add the amide product, stir at 0°C for 2 hours, then heat to 40°C, reflux and react with stirring at constant temperature for 1 hour, filter, extract and dry to obtain a modified flame retardant; the dosage ratio of phenylphosphoryl dichloride, toluene and amide product is 0.1 mol: 260 mL: 0.2 mol.

[0049] Embodiment 2: A modified flame retardant, the preparation of which comprises the following steps:

[0050] Step a1: In a nitrogen atmosphere, sodium benzaldehyde-2-sulfonate and acetic anhydride are added to a reaction bottle, reflux and stir, heat to 1670°C, and then potassium carbonate is added. The reaction is stirred at constant temperature for 25 hours, and the alkenyl carboxylic acid is obtained by extraction, rotary evaporation, and drying. The alkenyl carboxylic acid is added to DMF, and dithionyl chloride is added under stirring. The reaction is refluxed and stirred at 50°C for 4.5 hours to obtain an acyl chloride product. The amount ratio of sodium benzaldehyde-2-sulfonate, acetic anhydride, and potassium carbonate is 0.1 mol: 0.06 mol: 0.006 mol; the amount ratio of alkenyl carboxylic acid, DMF, and dithionyl chloride is 0.1 mol: 70 mL: 0.13 mol.

[0051] Step a2: N-aminoethylpiperazine, potassium carbonate and dimethyl sulfoxide are added to a flask to obtain a mixed solution 1, and then the acyl chloride product is added to dimethyl sulfoxide to obtain a mixed solution 2. The mixed solution 2 is slowly added dropwise to the mixed solution 1 in an ice-water bath at 0°C. After the addition is completed, the mixture is heated to 40°C, stirred at a constant temperature for 9 hours, and distilled under reduced pressure to obtain an amide product; the amount ratio of N-aminoethylpiperazine, potassium carbonate and dimethyl sulfoxide is 0.1 mol: 0.003 mol: 30 mL; the amount ratio of the acyl chloride product and dimethyl sulfoxide is 0.1 mol: 80 mL; the amount ratio of the mixed solution 1 to the mixed solution 2 is 35 mL: 85 mL;

[0052] Step a3: Add phenylphosphoryl dichloride to toluene, then add the amide product, stir at 5°C for 2h, then heat to 45°C, reflux and react with stirring at constant temperature for 1h, filter, extract and dry to obtain a modified flame retardant; the dosage ratio of phenylphosphoryl dichloride, toluene and amide product is 0.1mol:265mL:0.2mol.

[0053] Embodiment 3: A modified flame retardant, the preparation of which comprises the following steps:

[0054] Step a1: In a nitrogen atmosphere, sodium benzaldehyde-2-sulfonate and acetic anhydride are added to a reaction bottle, reflux and stir, heat to 170°C, and then potassium carbonate is added. The reaction is stirred at constant temperature for 26 hours, and the alkenyl carboxylic acid is obtained by extraction, rotary evaporation, and drying. The alkenyl carboxylic acid is added to DMF, and dithionyl chloride is added under stirring. The reaction is refluxed and stirred at 50°C for 5 hours to obtain an acyl chloride product. The dosage ratio of sodium benzaldehyde-2-sulfonate, acetic anhydride, and potassium carbonate is 0.1 mol: 0.07 mol: 0.008 mol; the dosage ratio of alkenyl carboxylic acid, DMF, and dithionyl chloride is 0.1 mol: 75 mL: 0.15 mol.

[0055] Step a2: N-aminoethylpiperazine, potassium carbonate and dimethyl sulfoxide are added to a flask to obtain a mixed solution 1, and then the acyl chloride product is added to dimethyl sulfoxide to obtain a mixed solution 2. The mixed solution 2 is slowly added dropwise to the mixed solution 1 in an ice-water bath at 0°C. After the addition is completed, the mixture is heated to 40°C, stirred at a constant temperature for 10 hours, and distilled under reduced pressure to obtain an amide product; the amount ratio of N-aminoethylpiperazine, potassium carbonate and dimethyl sulfoxide is 0.1 mol: 0.004 mol: 35 mL; the amount ratio of the acyl chloride product and dimethyl sulfoxide is 0.1 mol: 85 mL; the amount ratio of the mixed solution 1 to the mixed solution 2 is 40 mL: 90 mL;

[0056] Step a3: Add phenylphosphoryl dichloride to toluene, then add the amide product, stir at 5°C for 2 hours, then heat to 50°C, reflux and react with stirring at constant temperature for 1 hour, filter, extract and dry to obtain a modified flame retardant; the dosage ratio of phenylphosphoryl dichloride, toluene and amide product is 0.1 mol: 270 mL: 0.2 mol.

[0057] Embodiment 4: A modified filler, the preparation of which comprises the following steps:

[0058] Step b1: adding nano calcium carbonate to ethanol, ultrasonically dispersing for 30 minutes, obtaining solution 1 and adding it to a three-necked flask, then adding linoleic acid to ethanol, stirring at 50° C. for 35 minutes, obtaining solution 2 and adding it to the three-necked flask, turning on reflux stirring and reacting at 70° C. for 1 hour, and then filtering, drying and grinding to obtain modified calcium carbonate; the dosage ratio of nano calcium carbonate to ethanol is 10 g:30 mL, the dosage ratio of linoleic acid to ethanol is 0.1 mol:60 mL, the dosage ratio of solution 1 to solution 2 is 35 mL:65 mL, and the volume fraction of ethanol is 95%;

[0059] Step b2: Add modified calcium carbonate to dichloromethane, start stirring, then add 3-chloroperbenzoic acid, stir and react at room temperature for 4 hours to obtain an epoxy product; in a nitrogen atmosphere, add sorbic acid and ethanol to a flask, heat to 45°C, add pyridine, start stirring, add the epoxy product to the flask, stir and react for 8 hours, then heat to 105°C, stir for 1 hour, and obtain an esterification product; the amount ratio of modified calcium carbonate, dichloromethane and 3-chloroperbenzoic acid is 12g:50mL:0.1mol; the amount ratio of sorbic acid, ethanol, pyridine and epoxy product is 0.2mol:80mL:0.020mol:25g, and the volume fraction of ethanol is 95%;

[0060] Step b3: After mixing the esterification product and isocyanate, add 20% by mass dilute sulfuric acid solution and methanol, and react at 50°C for 4 hours to obtain a modified filler; the amount ratio of the esterification product, isocyanate, 20% by mass dilute sulfuric acid solution and methanol is 30g:0.2mol:100mL:300mL, and the isocyanate is 3,3,4,4,5,5,6,6,7,7,8,8,9,9,10,10,10-heptadecafluorodecyl isocyanate.

[0061] Embodiment 5: A modified filler, the preparation of which comprises the following steps:

[0062] Step b1: adding nano calcium carbonate to ethanol, ultrasonically dispersing for 30 minutes, obtaining solution 1 and adding it to a three-necked flask, then adding linoleic acid to ethanol, stirring at 55° C. for 40 minutes, obtaining solution 2 and adding it to the three-necked flask, turning on reflux stirring and reacting at 75° C. for 1.3 hours, and then filtering, drying and grinding to obtain modified calcium carbonate; the dosage ratio of nano calcium carbonate to ethanol is 10 g:35 mL, the dosage ratio of linoleic acid to ethanol is 0.1 mol:65 mL, the dosage ratio of solution 1 to solution 2 is 40 mL:70 mL, and the volume fraction of ethanol is 95%;

[0063] Step b2: Add modified calcium carbonate to dichloromethane, start stirring, then add 3-chloroperbenzoic acid, stir and react at room temperature for 4.5 hours to obtain an epoxy product; in a nitrogen atmosphere, add sorbic acid and ethanol to a flask, heat to 45°C, add pyridine, start stirring, add the epoxy product to the flask, stir and react for 9 hours, then heat to 110°C, stir for 1.5 hours to obtain an esterification product; the dosage ratio of modified calcium carbonate, dichloromethane and 3-chloroperbenzoic acid is 13g:55mL:0.1mol; the dosage ratio of sorbic acid, ethanol, pyridine and epoxy product is 0.2mol:85mL:0.023mol:26g, and the volume fraction of ethanol is 95%;

[0064] Step b3: After mixing the esterification product and isocyanate, add 20% by mass of dilute sulfuric acid solution and methanol, and react at 50°C for 4 hours to obtain a modified filler; the amount ratio of the esterification product, isocyanate, 20% by mass of dilute sulfuric acid solution and methanol is 31g:0.2mol:100mL:310mL, and the isocyanate is 3,3,4,4,5,5,6,6,7,7,8,8,9,9,10,10,10-heptadecafluorodecyl isocyanate.

[0065] Embodiment 6: A modified filler, the preparation of which comprises the following steps:

[0066] Step b1: adding nano calcium carbonate to ethanol, ultrasonically dispersing for 30 minutes, obtaining solution 1 and adding it to a three-necked flask, then adding linoleic acid to ethanol, stirring at 60° C. for 45 minutes, obtaining solution 2 and adding it to the three-necked flask, turning on reflux stirring and reacting at 80° C. for 1.5 hours, and then filtering, drying and grinding to obtain modified calcium carbonate; the dosage ratio of nano calcium carbonate to ethanol is 10 g:40 mL, the dosage ratio of linoleic acid to ethanol is 0.1 mol:70 mL, the dosage ratio of solution 1 to solution 2 is 45 mL:75 mL, and the volume fraction of ethanol is 95%;

[0067] Step b2: Add modified calcium carbonate to dichloromethane, start stirring, then add 3-chloroperbenzoic acid, stir and react at room temperature for 5 hours to obtain an epoxy product; in a nitrogen atmosphere, add sorbic acid and ethanol to a flask, heat to 45°C, add pyridine, start stirring, add the epoxy product to the flask, stir and react for 10 hours, then heat to 115°C, stir for 2 hours to obtain an esterification product; the dosage ratio of modified calcium carbonate, dichloromethane and 3-chloroperbenzoic acid is 14g:60mL:0.1mol; the dosage ratio of sorbic acid, ethanol, pyridine and epoxy product is 0.2mol:90mL:0.025mol:27g, and the volume fraction of ethanol is 95%;

[0068] Step b3: After mixing the esterification product and isocyanate, add 20% by mass dilute sulfuric acid solution and methanol, and react at 50°C for 4 hours to obtain a modified filler; the amount ratio of the esterification product, isocyanate, 20% by mass dilute sulfuric acid solution and methanol is 32g:0.2mol:100mL:320mL, and the isocyanate is 3,3,4,4,5,5,6,6,7,7,8,8,9,9,10,10,10-heptadecafluorodecyl isocyanate.

[0069] Example 7: Figure 1A fireproof composite low-voltage cable is shown, comprising a cable A, a signal line B, a tape layer C and an outer sheath D; a plurality of the cable A and a plurality of the signal lines B are evenly placed in the tape layer C, the tape layer C is coated on the outer periphery of the cable A and the signal line B, and the outer sheath D is coated on the outer periphery of the tape layer C;

[0070] The innermost layer of the cable A is a copper conductor AⅠ, and the outer periphery of the copper conductor AⅠ is coated with an insulating layer AⅡ; the insulating layer AⅡ is made of cross-linked polyethylene material; the innermost layer of the signal line B is an optical fiber core bundle BⅠ, and the outer periphery of the optical fiber core bundle BⅠ is sequentially coated with a shielding layer BⅡ, a heat insulation layer BⅢ, and an optical cable sheath tube BⅣ; the shielding layer BⅡ is made of an electric shielding wire and a magnetic shielding wire woven into a mesh structure, the electric shielding wire is a copper wire, and the magnetic shielding wire is an iron wire; the heat insulation layer BⅢ is made of silicone rubber, and the optical cable sheath tube BⅣ is a nylon loose tube; the wrapping tape Layer C is obtained by wrapping a polyester tape; the outer sheath D is made of a polyurethane cable material, and the polyurethane cable material includes the following raw materials in parts by weight: 45 parts of thermoplastic polyurethane, 10 parts of ethylene-vinyl acetate copolymer, 15 parts of modified flame retardant, 3 parts of antioxidant, 2 parts of lubricant, 1 part of light stabilizer and 10 parts of modified filler; the antioxidant is a mixture of antioxidant 1010 and antioxidant 618 in a mass ratio of 3:1, the lubricant is polyethylene wax, and the light stabilizer is 2,2'-hydroxy-4-methoxybenzophenone;

[0071] The preparation of the fireproof composite low-voltage cable comprises the following steps:

[0072] Step S1: extruding a cross-linked polyethylene material around the outer periphery of a copper conductor to form an insulating layer to obtain a cable;

[0073] Step S2: copper wires and iron wires are braided into a mesh structure and then coated on the outer periphery of the optical fiber core bundle to form a shielding layer; silicone rubber is then extruded on the outer periphery of the shielding layer to form a heat insulation layer; and nylon loose tube is then coated on the outer periphery of the heat insulation layer to form an optical cable sheath tube to obtain a signal line;

[0074] Step S3: adding ethylene-vinyl acetate copolymer, the modified flame retardant obtained in Example 1, an antioxidant, a lubricant, a light stabilizer and the modified filler obtained in Example 4 to a high-speed mixer, stirring at a speed of 250 r / min and a temperature of 80° C. for 10 min to obtain a mixture, transferring the mixture to an internal mixer, adding thermoplastic polyurethane and internally mixing for 8 min to obtain a polyurethane cable material;

[0075] Step S4: evenly place 8 cables and 6 signal lines, wrap some of the cables and some of the signal lines with polyester tape to form a tape layer; then extrude polyurethane cable material around the tape layer to form an outer sheath to obtain a fireproof composite low-voltage cable.

[0076] Example 8: Figure 1 A fireproof composite low-voltage cable is shown, comprising a cable A, a signal line B, a tape layer C and an outer sheath D; a plurality of the cable A and a plurality of the signal lines B are evenly placed in the tape layer C, the tape layer C is coated on the outer periphery of the cable A and the signal line B, and the outer sheath D is coated on the outer periphery of the tape layer C;

[0077] The innermost layer of the cable A is a copper conductor AⅠ, and the outer periphery of the copper conductor AⅠ is coated with an insulating layer AⅡ; the insulating layer AⅡ is made of cross-linked polyethylene material; the innermost layer of the signal line B is an optical fiber core bundle BⅠ, and the outer periphery of the optical fiber core bundle BⅠ is sequentially coated with a shielding layer BⅡ, a heat insulation layer BⅢ, and an optical cable sheath tube BⅣ; the shielding layer BⅡ is made of an electric shielding wire and a magnetic shielding wire woven into a mesh structure, the electric shielding wire is a copper wire, and the magnetic shielding wire is an iron wire; the heat insulation layer BⅢ is made of silicone rubber, and the optical cable sheath tube BⅣ is a nylon loose tube; the wrapping tape Layer C is obtained by wrapping a polyester tape; the outer sheath D is made of a polyurethane cable material, and the polyurethane cable material includes the following raw materials in parts by weight: 50 parts of thermoplastic polyurethane, 13 parts of ethylene-vinyl acetate copolymer, 20 parts of modified flame retardant, 4 parts of antioxidant, 3 parts of lubricant, 2 parts of light stabilizer and 11 parts of modified filler; the antioxidant is a mixture of antioxidant 1010 and antioxidant 618 in a mass ratio of 3:1, the lubricant is polyethylene wax, and the light stabilizer is 2,2'-hydroxy-4-methoxybenzophenone;

[0078] The preparation of the fireproof composite low-voltage cable comprises the following steps:

[0079] Step S1: extruding a cross-linked polyethylene material around the outer periphery of a copper conductor to form an insulating layer to obtain a cable;

[0080] Step S2: copper wires and iron wires are braided into a mesh structure and then coated on the outer periphery of the optical fiber core bundle to form a shielding layer; silicone rubber is then extruded on the outer periphery of the shielding layer to form a heat insulation layer; and nylon loose tube is then coated on the outer periphery of the heat insulation layer to form an optical cable sheath tube to obtain a signal line;

[0081] Step S3: adding ethylene-vinyl acetate copolymer, the modified flame retardant obtained in Example 2, an antioxidant, a lubricant, a light stabilizer and the modified filler obtained in Example 5 to a high-speed mixer, stirring at a speed of 270 r / min and a temperature of 85° C. for 15 minutes to obtain a mixture, transferring the mixture to an internal mixer, adding thermoplastic polyurethane and internally mixing for 9 minutes to obtain a polyurethane cable material;

[0082] Step S4: Evenly place 9 cables and 7 signal lines, wrap some of the cables and signal lines with polyester tape to form a tape layer; then extrude polyurethane cable material around the tape layer to form an outer sheath to obtain a fireproof composite low-voltage cable.

[0083] Example 9: Figure 1 A fireproof composite low-voltage cable is shown, comprising a cable A, a signal line B, a tape layer C and an outer sheath D; a plurality of the cable A and a plurality of the signal lines B are evenly placed in the tape layer C, the tape layer C is coated on the outer periphery of the cable A and the signal line B, and the outer sheath D is coated on the outer periphery of the tape layer C;

[0084] The innermost layer of the cable A is a copper conductor AⅠ, and the outer periphery of the copper conductor AⅠ is coated with an insulating layer AⅡ; the insulating layer AⅡ is made of cross-linked polyethylene material; the innermost layer of the signal line B is an optical fiber core bundle BⅠ, and the outer periphery of the optical fiber core bundle BⅠ is sequentially coated with a shielding layer BⅡ, a heat insulation layer BⅢ, and an optical cable sheath tube BⅣ; the shielding layer BⅡ is made of an electric shielding wire and a magnetic shielding wire woven into a mesh structure, the electric shielding wire is a copper wire, and the magnetic shielding wire is an iron wire; the heat insulation layer BⅢ is made of silicone rubber, and the optical cable sheath tube BⅣ is a nylon loose tube; the wrapping tape Layer C is obtained by wrapping a polyester tape; the outer sheath D is made of a polyurethane cable material, and the polyurethane cable material includes the following raw materials in parts by weight: 55 parts of thermoplastic polyurethane, 15 parts of ethylene-vinyl acetate copolymer, 25 parts of modified flame retardant, 5 parts of antioxidant, 4 parts of lubricant, 3 parts of light stabilizer and 12 parts of modified filler; the antioxidant is a mixture of antioxidant 1010 and antioxidant 618 in a mass ratio of 3:1, the lubricant is polyethylene wax, and the light stabilizer is 2,2'-hydroxy-4-methoxybenzophenone;

[0085] The preparation of the fireproof composite low-voltage cable comprises the following steps:

[0086] Step S1: extruding a cross-linked polyethylene material around the outer periphery of a copper conductor to form an insulating layer to obtain a cable;

[0087] Step S2: copper wires and iron wires are braided into a mesh structure and then coated on the outer periphery of the optical fiber core bundle to form a shielding layer; silicone rubber is then extruded on the outer periphery of the shielding layer to form a heat insulation layer; and nylon loose tube is then coated on the outer periphery of the heat insulation layer to form an optical cable sheath tube to obtain a signal line;

[0088] Step S3: adding ethylene-vinyl acetate copolymer, the modified flame retardant obtained in Example 3, an antioxidant, a lubricant, a light stabilizer and the modified filler obtained in Example 6 to a high-speed mixer, stirring at a speed of 300 r / min and a temperature of 90° C. for 20 min to obtain a mixture, transferring the mixture to an internal mixer, adding thermoplastic polyurethane and internally mixing for 10 min to obtain a polyurethane cable material;

[0089] Step S4: evenly place 10 cables and 8 signal lines, wrap some of the cables and some of the signal lines with polyester tape to form a tape layer; then extrude polyurethane cable material around the tape layer to form an outer sheath to obtain a fireproof composite low-voltage cable.

[0090] Comparative Example 1: Compared with Example 9, the modified flame retardant is replaced with the amide product obtained in step a2 of Example 3, and the rest is exactly the same as Example 9 to prepare a fire-proof composite low-voltage cable.

[0091] Comparative Example 2: Compared with Example 9, the modified filler is replaced with the modified calcium carbonate obtained in step b1 of Example 6, and the rest is exactly the same as Example 9 to prepare a fire-proof composite low-voltage cable.

[0092] The fireproof composite low-voltage cable prepared by the present invention is further tested for its effectiveness, and the test results are as follows.

[0093] In order to test the fireproof composite low-voltage cable prepared by the present invention, the performance test of the polyurethane cable material used in the outer sheath of the fireproof composite low-voltage cable obtained in Examples 7-9 and Comparative Examples 1-2 was carried out, and the tensile strength and elongation at break were tested according to GB / T2951.11-2008 "General Test Methods for Insulation and Sheath Materials of Electric and Optical Cables"; the oxygen index was tested according to GB / T2406.1-2008 "Determination of Combustion Behavior of Plastics by Oxygen Index Method"; the rat-proof performance was tested according to GB / T34016-2017 "General Rules for Rat-proof and Ant-proof Wires and Cables"; the rat-proof performance was tested according to GB / T3140 2-2015 "Test Method for Antibacterial Performance of Plastic Surface" Antibacterial performance test was carried out with Escherichia coli and Staphylococcus aureus as the test bacteria, and the sample size of the polyurethane cable material was 2mm×40mm×40mm; Waterproof performance test method: 150.0g of the fireproof composite low-voltage cable sample obtained by Examples 7-9 and Comparative Examples 1-2 was immersed in water (water temperature 15°C), and the two ends of the sample were sealed and extended 300mm above the water surface. After soaking for one week, the weight after soaking was measured and the outer sheath was removed after soaking to observe whether there was moisture on the outer surface; the test results are recorded in Table 1;

[0094] Table 1: Test results

[0095]

[0096] According to the data in Table 1, the polyurethane cable material used in the outer sheath of the fireproof composite low-voltage cable prepared by the present invention has excellent mechanical properties, flame retardancy, rodent resistance, antibacterial and waterproof properties, and improves the mechanical properties, flame retardancy, rodent resistance, antibacterial and waterproof properties of the fireproof composite low-voltage cable. Compared with Comparative Example 1, Example 9 uses a modified flame retardant with a phosphoramide structure, which synergistically flame retards with the sodium sulfonate group in the same molecule, significantly improving the flame retardancy of the cable. Compared with Comparative Example 2, Example 9 uses a modified filler with a sorbate group, an isocyanate group and a fluorinated alkane long chain to improve the antibacterial and waterproof properties of the cable.

[0097] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A fireproof composite low-voltage cable, characterized in that: It comprises a cable line A, a signal line B, a tape layer C and an outer sheath D; a plurality of the cable lines A and a plurality of the signal lines B are evenly placed in the tape layer C, the tape layer C is coated on the outer periphery of the cable line A and the signal line B, and the outer sheath D is coated on the outer periphery of the tape layer C; the outer sheath D is made of a polyurethane cable material, and the polyurethane cable material comprises the following raw materials in parts by weight: 45-55 parts of thermoplastic polyurethane, 10-15 parts of ethylene-vinyl acetate copolymer, 15-25 parts of modified flame retardant, 3-5 parts of antioxidant, 2-4 parts of lubricant, 1-3 parts of light stabilizer and 10-12 parts of modified filler; The modified flame retardant is prepared by the following steps: Step a1: In a nitrogen atmosphere, sodium benzaldehyde-2-sulfonate and acetic anhydride are added to a reaction bottle, refluxed and stirred, and the temperature is raised to 150-170° C., and potassium carbonate is added, and the reaction is stirred under reflux at a constant temperature for 24-26 hours, and the alkenyl carboxylic acid is extracted, rotary evaporated, and dried to obtain the alkenyl carboxylic acid; the alkenyl carboxylic acid is added to DMF, and dithionyl chloride is added under stirring, and the reaction is stirred under reflux at 50° C. for 4-5 hours to obtain the acyl chloride product; Step a2: Add N-aminoethylpiperazine, potassium carbonate and dimethyl sulfoxide into a flask to obtain a mixed solution 1, then add the acyl chloride product into dimethyl sulfoxide to obtain a mixed solution 2, slowly dropwise add the mixed solution 2 into the mixed solution 1 in an ice-water bath at 0°C, after the dropwise addition is completed, heat to 40°C, stir and react at a constant temperature for 8-10 hours, and distill under reduced pressure to obtain an amide product; Step a3: Add phenylphosphoryl dichloride to toluene, then add the amide product, stir at 0-5°C for 2h, then heat to 40-50°C, reflux and react with stirring at constant temperature for 1h, filter, extract and dry to obtain the modified flame retardant.

2. A fireproof composite low-voltage cable according to claim 1, characterized in that: In step a1, the usage ratio of sodium benzaldehyde-2-sulfonate, acetic anhydride and potassium carbonate is 0.1 mol: 0.05-0.07 mol: 0.005-0.008 mol; the usage ratio of alkenyl carboxylic acid, DMF and dichlorothionyl is 0.1 mol: 65-75 mL: 0.12-0.15 mol.

3. A fireproof composite low-voltage cable according to claim 1, characterized in that: In step a2, the usage ratio of N-aminoethylpiperazine, potassium carbonate and dimethyl sulfoxide is 0.1 mol: 0.002-0.004 mol: 25-35 mL; the usage ratio of acyl chloride product and dimethyl sulfoxide is 0.1 mol: 75-85 mL; and the usage ratio of mixed solution 1 and mixed solution 2 is 30-40 mL: 80-90 mL.

4. A fireproof composite low-voltage cable according to claim 1, characterized in that: In step a3, the usage ratio of phenylphosphoryl dichloride, toluene and amide product is 0.1 mol: 260-270 mL: 0.2 mol.

5. The fireproof composite low-voltage cable according to claim 1, characterized in that: The modified filler is prepared by the following steps: Step b1: adding nano calcium carbonate to ethanol, ultrasonically dispersing for 30 minutes, obtaining solution 1 and adding it to a three-necked flask, then adding linoleic acid to the ethanol, stirring at 50-60° C. for 35-45 minutes, obtaining solution 2 and adding it to the three-necked flask, turning on reflux stirring and reacting at 70-80° C. for 1-1.5 hours, and then filtering, drying and grinding to obtain modified calcium carbonate; Step b2: Add modified calcium carbonate to dichloromethane, start stirring, then add 3-chloroperoxybenzoic acid, stir and react at room temperature for 4-5 hours to obtain the epoxy product; in a nitrogen atmosphere, add sorbic acid and ethanol to a flask, heat to 45°C, add pyridine, start stirring, add the epoxy product to the flask, stir and react for 8-10 hours, then heat to 105-115°C, stir for 1-2 hours to obtain the esterification product; Step b3: After mixing the esterification product and isocyanate, add 20% by mass of dilute sulfuric acid solution and methanol, and react at 50° C. for 4 hours to obtain a modified filler.

6. A fireproof composite low-voltage cable according to claim 5, characterized in that: In step b1, the usage ratio of nano-calcium carbonate and ethanol is 10g:30-40mL, the usage ratio of linoleic acid and ethanol is 0.1mol:60-70mL, the usage ratio of solution 1 and solution 2 is 35-45mL:65-75mL, and the volume fraction of ethanol is 95%.

7. The fireproof composite low-voltage cable according to claim 5, characterized in that: In step b2, the usage ratio of modified calcium carbonate, dichloromethane and 3-chloroperbenzoic acid is 12-14 g: 50-60 mL: 0.1 mol; the usage ratio of sorbic acid, ethanol, pyridine and epoxidation product is 0.2 mol: 80-90 mL: 0.020-0.025 mol: 25-27 g, and the volume fraction of ethanol is 95%.

8. The fireproof composite low-voltage cable according to claim 5, characterized in that: In step b3, the amount ratio of the esterification product, isocyanate, 20% dilute sulfuric acid solution and methanol is 30-32 g: 0.2 mol: 100 mL: 300-320 mL, and the isocyanate is 3,3,4,4,5,5,6,6,7,7,8,8,9,9,10,10,10-heptadecafluorodecyl isocyanate.

9. The fireproof composite low-voltage cable according to claim 1, characterized in that: The innermost layer of the cable A is a copper conductor AⅠ, and the outer periphery of the copper conductor AⅠ is coated with an insulating layer AⅡ; the insulating layer AⅡ is made of cross-linked polyethylene material; the innermost layer of the signal line B is an optical fiber core bundle BⅠ, and the outer periphery of the optical fiber core bundle BⅠ is coated with a shielding layer BⅡ, a thermal insulation layer BⅢ, and an optical cable sheath tube BⅣ in sequence; the shielding layer BⅡ is made of an electric shielding wire and a magnetic shielding wire woven into a mesh structure, the electric shielding wire is a copper wire, and the magnetic shielding wire is an iron wire; the thermal insulation layer BⅢ is made of silicone rubber, and the optical cable sheath tube BⅣ is a nylon loose tube; the tape layer C is obtained by wrapping a polyester tape; the antioxidant is a mixture of antioxidant 1010 and antioxidant 618 in a mass ratio of 3:1, the lubricant is polyethylene wax, and the light stabilizer is 2,2'-hydroxy-4-methoxybenzophenone.

10. The method for preparing a fireproof composite low-voltage cable according to claim 1, characterized in that: The steps include: Step S1: extruding a cross-linked polyethylene material around the outer periphery of a copper conductor to form an insulating layer to obtain a cable; Step S2: copper wires and iron wires are braided into a mesh structure and then coated on the outer periphery of the optical fiber core bundle to form a shielding layer; silicone rubber is then extruded on the outer periphery of the shielding layer to form a heat insulation layer; and nylon loose tube is then coated on the outer periphery of the heat insulation layer to form an optical cable sheath tube to obtain a signal line; Step S3: adding ethylene-vinyl acetate copolymer, modified flame retardant, antioxidant, lubricant, light stabilizer and modified filler to a high-speed mixer, stirring at a speed of 250-300 r / min and a temperature of 80-90° C. for 10-20 min to obtain a mixture, transferring the mixture to an internal mixer, adding thermoplastic polyurethane and internal mixing for 8-10 min to obtain a polyurethane cable material; Step S4: evenly place a number of cables and a number of signal lines, wrap the outer circumference of the cables and the signal lines with polyester tape to form a tape layer; then extrude the polyurethane cable material on the outer circumference of the tape layer to form an outer sheath, and obtain a fireproof composite low-voltage cable.

Citation Information

Patent Citations

  • Polyamide intumescent flame-retardant char-forming agent having main chain containing piperazine structure and preparation method and application thereof

    CN105669970A

  • Preparation method of halogen-free flame-retardant polycaprolactam composite material

    CN107298853A

  • Flame retardant containing phosphorus-nitrogen vinyl monomer and synthesis method thereof

    CN109776725A

  • Polyurethane foams, adhesive tapes, their uses, and a method for producing polyurethane foams

    CN110903453A

  • Comprehensive flexible cable and manufacturing method thereof

    CN113299440A

Cited By

  • Tensile composite cable for robot and preparation method thereof

    CN120527071A

  • A tensile-resistant composite cable for a robot and a method of manufacturing the same

    CN120527071B